Модель перетворення коштів трудових мігрантів у механізм забезпечення сталого розвитку громад - Химинець, В.В.; Цімболинець, Г.І. (Економіка природокористування і сталий розвиток, 2019)
Проаналізовано актуальні дані щодо основних аспектів міжнародної трудової міграції України, а саме: кількості мігрантів, їх основних сфер зайнятості, найбільших країн-реципієнтів та регіонів-донорів трудових мігрантів, обсягів грошових переказів і заощаджень мігрантів. Наведено схему формування інвестиційного кластера об’єднаної територіальної громади, базисом якого є процес взаємодії між керівництвом громади, науковцями та експертами вищих навчальних закладів, Центрів надання адміністративних послуг і трудових мігрантів як потенційних внутрішніх інвесторів. This scientific paper is devoted to developing ways and models of converting the laboк migrants cost into the internal investment resources of United Territorial Communities, taking into account their new functions and powers.
The article analyzes current data on the main aspects of Ukraine's international labor migration, namely: the number of migrants, their main employment areas, the largest recipient countries of labor migrants and donor regions, the amount of remittances and savings of migrants.
In Ukraine, 882 United Territorial Communities have already been formed, which have received considerable authority from developing a development strategy to landscaping, approving a budget, setting local taxes and fees, defining social and cultural development. Considering the results of the research on the amount of cash flows, the availability of savings and the desire of many migrant workers to return to Ukraine, it can be argued that they have a huge potential to become one of the largest domestic investors of the United Territorial Communities. Therefore, migrants have resources, and UTCs have considerable authority to attract these resources.
The authors present a scheme for forming an investment cluster of united territorial communities, the basis of which is the process of interaction between community leadership, academics and experts of higher education institutions, administrative services centers and migrant workers as potential domestic investors.
The implementation and effective functioning of this model will create incentives for migrants to return and benefit from productive usage of their resources, as they will be able to earn enough income to keep families and create jobs for other residents. The community, in turn, will benefit from new tax revenues and other payments, the development of human potential and the formation of a positive image of the territory as a successful business environment.